Mechanical Properties Improvement of CoCrFeMnNiB0.1 High Entropy Alloy through Annealing Design. Issue 2 (2nd April 2020) - Hou, Lili; Hui, Jiatao; Yao, Yuhong; Chen, Jian; Liu, Jiangnan
ABSTRACT: XRD results show that diffraction peak of M3 B is gradually apparent with the increase of annealing temperature and time, which indicates that annealing can promote the formation of M3 B phase. The increase of annealing temperature and time leads to transformation of inter dendritic microstructure from long strip Cr3 B phase to granular Cr3 B phase. Particularly, after annealing at 1100 o C for 20 h, the particles of Cr3 B phase are distributed homogeneously in the matrix FCC phase, but the number of Cr3 B phase decreases evidently. After annealing at 1100 o C for 20 h, the yield strength and tensile strength of the alloy become 412 MPa and 797 MPa, having increments of 64.1% and 70.7%, respectively, compared to the as-cast alloys. However, the elongation remains the same as the cast alloy. After annealing, the particles of Cr3 B phase are uniformly distributed in the FCC matrix and some B elements are dissolved into dendritic structure which results in significant increase of strength in the form of dispersion strengthening and solution strengthening. TEM images of the samples depict that after annealing certain deformation twins are observed, which lead to the maintenance of plasticity. GRAPHICAL ABSTRACT: